Causes and mechanisms of occurrence most common injuries of kayakers - Kricka, O.; Petak, S.; Prlenda, N.; Maglov, M. (The proceedings book of 1st International Conference on Science and Medicine in Aquatic Sports : Split, Croatia, 1st - 4th September 2022., 2022)
For the past few years, kayaking has been a sport in which interest is growing rapidly. Increasing number of athletes and recreational athletes engage in this activity, so does the percentage of injuries. The aim of this research was to show the most often injuries among paddlers, the mechanisms of their occurrence in order to better prepare and prevent. We searched through 3 databases. When searching the databases, the keywords "kayak", "kayaking", "injuries", "prevention" were used in different variants. Insight into previous research on the topic of injuries in kayakers, the emphasis is placed on the upper body, mostly on the shoulder. The cause of these injuries is attributed by most authors to improper rowing technique, muscle asymmetry, blows to various objects or objects on the water and excessive performance that leads to fatigue, and eventually to the possibility of injury. Chronic injuries, typically of the upper extremity, are quite common among rowers and are most often related to the shoulders, as evidenced by the largest number of studies. There are several external and internal factors that affect the potential injury of a kayaker. To reduce it, it is important to perform preventive actions such as better information, better warm-up, improvement of technique and dosing the amount of training, which is especially difficult for elite athletes.